2008
DOI: 10.1080/10428190802345902
|View full text |Cite
|
Sign up to set email alerts
|

Characterising the TP53-deleted subgroup of chronic lymphocytic leukemia: an analysis of additional cytogenetic abnormalities detected by interphase fluorescencein situhybridisation and array-based comparative genomic hybridisation

Abstract: Deletion of the TP53 gene on chromosome 17p13.1 is the prognostic factor associated with the shortest survival in CLL. We used array-based comparative genomic hybridisation (arrayCGH) to identify additional DNA copy number changes in peripheral blood samples from 74 LRF CLL4 trial patients, 37 with >or=5% and 37 without TP53-deleted cells. ArrayCGH reliably detected deletions on 17p, including the TP53 locus, in cases with >or=50%TP53-deleted cells detected by fluorescence in situ hybridisation, plus seven add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
1
9
0
1
Order By: Relevance
“…In addition, an increased expression of CD38, ZAP-70, and unmutated IGHV was reported in 17p- cases, which agrees with the poor prognosis of this group of patients [31, 66, 67]. Other studies have demonstrated a significant correlation between 17p- and 4p-, 18p-, 20p-, or chromosome 8 alterations (8p- or 8q+) [30, 68]. Thus, TP53 mutation/17p- is correlated with a higher genetic complexity.…”
Section: Cytogenetic Aberrations With Known Prognostic Valuesupporting
confidence: 76%
“…In addition, an increased expression of CD38, ZAP-70, and unmutated IGHV was reported in 17p- cases, which agrees with the poor prognosis of this group of patients [31, 66, 67]. Other studies have demonstrated a significant correlation between 17p- and 4p-, 18p-, 20p-, or chromosome 8 alterations (8p- or 8q+) [30, 68]. Thus, TP53 mutation/17p- is correlated with a higher genetic complexity.…”
Section: Cytogenetic Aberrations With Known Prognostic Valuesupporting
confidence: 76%
“…Previous retrospective studies based on FISH, comparative genomic hybridization (aCGH) and SNP array identified 2p gain as a recurrent alteration in CLL associated with advanced Binet stage, UM status of IGHV gene and 17p13 deletion [12,[14][15][16][17][18][19][20][21][22]24,[39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…It has, therefore, been suggested that alternative therapies may be needed to manage those patients with a TP53 defective pathway, as traditional therapies such as the use of fludarabine and cyclophosphamide have been found ineffective (Catovsky et al , 2007; Grever et al , 2007). Similarly, inferior response to treatment and low rate of overall and progression‐free survival were found to be characteristics of CLL patients with a high percentage of TP53 ‐deleted cells in their peripheral blood (Rudenko et al , 2008). Finally, in a study that analyzed a series of cell cycle regulatory proteins including CDKN1A (also called p21 Waf1 ), p27 Kip2 , retinoblastoma (Rb) and cyclin D1 in relation to TP53 in CLL and its transformed disease state, Richter syndrome, it was found that the pattern of overexpression of TP53 and under‐expression of CDKN1A was significantly associated with TP53 mutations.…”
Section: Tp53 Status and Its Prognostic Value In Lymphoid Malignanciesmentioning
confidence: 99%